1999
DOI: 10.34024/rnc.2008.v16.8614
|View full text |Cite
|
Sign up to set email alerts
|

Bruxism as mechanism subserving hysteria

Abstract: Objective. To explore the hypothesis that bruxism is a mechanism in hysteria by comparing features in hysteria, bruxism, hostility, and local complaints in bruxers. Method. We evaluated 33 patients with mild bruxism, 52 with moderate, 55 with severe, and 42 with extreme bruxism with the Minnesota Multiphasic Personality Index and the Cook-Medley scale for hostility. Results. Scores of hysteria and hostility increased from the mild to the moderate, severe, and extreme bruxism subgroup (p<0.0001). Mean local … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
1
7
0
2
Order By: Relevance
“…In There has been an increasing interest in the relationship between sleep problems and mental health. Bruxing behavior was observed in those with higher Hy scores of MMPI, indicating that there was a close relationship between Hy and bruxing behavior [22]. The mean anxiety scores of the Hospital Anxiety Depression Scales and the Hamilton Anxiety Rating Scale were statistically significant higher in patients with bruxism compared with those without bruxism.…”
Section: Discussionmentioning
confidence: 83%
“…In There has been an increasing interest in the relationship between sleep problems and mental health. Bruxing behavior was observed in those with higher Hy scores of MMPI, indicating that there was a close relationship between Hy and bruxing behavior [22]. The mean anxiety scores of the Hospital Anxiety Depression Scales and the Hamilton Anxiety Rating Scale were statistically significant higher in patients with bruxism compared with those without bruxism.…”
Section: Discussionmentioning
confidence: 83%
“…In one study in CMDs individuals 14 , researchers reported higher scores in hysteria and greater number of painful sites with the severity of BB. Because hysteria is closely related with both somatization and with DID in many CMDs individuals, such disorders may increase the need for medication use in many CMDs patients.…”
Section: Discussionmentioning
confidence: 97%
“…Patients were classified as presenting CMDs if they demonstrated specific signs/symptoms, including a complaint of pain in the masticatory muscles, noises in the TMJs, difficulties to perform lateral and/or opening jaw movements, tenderness in the masticatory muscles during palpation and headaches usually of muscular origin. Patients were classified as presenting CMDs and BB according to criteria published previously 14 . Only those charts presenting clear, sufficient and accurate information defining the most common types of headache pain were reviewed and included in the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kampe and coworkers (17), reported that compared to less frequent bruxers and the general population, the more frequent bruxers presented higher scores in the somatic anxiety, the muscular tension and in the psychic anxiety scales indicating that they were more vulnerable to anxiety, muscle tension and psychosomatic disorders. Additionally, one recent study (19), reported higher scores for anxiety, hysteria, somatization and hostility in severe and extreme bruxing behavior with facial pains and headaches. Additionally, MPD patients with facial pain non responding to conventional therapy showed a greater overall degree of emotional distress.…”
Section: Severe Psychological Disordersmentioning
confidence: 95%